Odpowiedzi

2009-12-09T19:58:59+01:00
A/3 + b/5= 7
a/4 -b/5=0

a/3 + a/4 = 7
4a/12 + 3a/12 = 7
4a/12 = 7 |*12
4a = 84 |:4
a = 21

a/3 + b/5 = 7
21/3 + b/5 = 7
b/5 = 7 - 7
b/5 = 0
b = 0

k/3 +1/4 =1
k/4+1/8 =1

k/4 + 1/8 = k/3 + 1/4
k/4 - k/3 = 1/4 - 1/8
3k/12 - 4k/12 = 1/4 - 2/4
-k/12 = -1/4 |*(-12)
k = 1/4 * 12
k = 3
Tutaj nie było drugiej literki? same k?



5x - 5y =2,5 |*3
7y+ 3x =14,5 |*5

15x - 15y = 7,5
15x + 35y = 72,5

15x = 7,5 + 15y

7,5 + 15y + 35y = 72,5
15y + 35y = 72,5 - 7,5
50y = 65 |:50
y = 1,3


5x - 5y =2,5
5x = 2,5 + 5y
5x = 2,5 + 5*1,3
5x = 2,5 + 6,5
5x = 9 |:5
x = 1,8
1 2 1
2009-12-09T20:04:07+01:00
A/3 + b/5= 7 /*15
a/4 -b/5=0

5a + 3b = 105
a/4 = b/5 /*20

5a = 105 - 3b
a = 4/5 b

4b = 105 - 3b
a = 4/5 b

7b = 105
a = 4/5 b

b = 15
a = 12

W tym zadaniu chyba cos pomyliles
k/3 +1/4 =1 /*3
k/4+1/8 =1 /*4

k + 0,75 = 3
k + 0,5 = 4

k = 2,25
k = 3,5

5x - 5y =2.5 /:5
7y+ 3x =14,5

x - y = 0,5
7y + 3x = 14,5

x = 0,5 + y
7y + 3*(0,5 +y) = 14,5

x= 0,5 + y
7y + 1,5 + 3y = 14,5

x = 0,5 + y
10y = 13 /10

x = 0,5 + y
y = 1,3

x = 1,8
y = 1,3
1 5 1